1995
DOI: 10.1037/0735-7044.109.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a microinjection of morphine into the amygdala on the acquisition and expression of conditioned fear and hypoalgesia in rats.

Abstract: A unilateral microinjection of morphine into the amygdala impaired the acquisition of fear and hypoalgesic responses in rats exposed to a heated floor in a hot-plate apparatus. This impairment was dose dependent, receptor specific, and not observed in rats microinjected with morphine into the caudal basolateral amygdala. A microinjection of morphine into the amygdala reduced the expression of fear responses and of naloxone-sensitive hypoalgesic responses, but did not reduce the expression of naloxone-insensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…Although previous studies have shown that acute microinjection of morphine into the amygdala or nucleus accumbens impairs the acquisition and expression of fear memory [25,26] , little is known about the effect of chronic morphine on fear memory. We found that morphine withdrawal in mice did not affect the acquisition of contextual or cued fear responses, but inhibited the extinction of the cued fear response.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that acute microinjection of morphine into the amygdala or nucleus accumbens impairs the acquisition and expression of fear memory [25,26] , little is known about the effect of chronic morphine on fear memory. We found that morphine withdrawal in mice did not affect the acquisition of contextual or cued fear responses, but inhibited the extinction of the cued fear response.…”
Section: Discussionmentioning
confidence: 99%
“…The right vlPAG was targeted so that the tip of the guide cannula was positioned 5.6 mm below lambda through a hole drilled 0.1 mm anterior to and 0.8 mm lateral to lambda. We implanted cannula into only one hemisphere for two reasons: First, to reduce the possible extent of damage to the PAG and overlying blood vessels; second, because previous research has demonstrated that a unilateral manipulation was sufficient to observe an effect on fear conditioning in a number of brain regions critical for this learning (for example, see Good and Westbrook 1995;LaBar and LeDoux 1996;McNally and Cole 2006). We chose the right PAG to facilitate comparison with our previous experiments (McNally and Cole 2006).…”
Section: Surgery and Histologymentioning
confidence: 99%
“…Local infusion of benzodiazepine agonists into the amygdala produces anxiolytic effects which can be blocked by co-administration of GABA A or benzodiazepine antagonists (Scheel-Kruger and Petersen 1982;Petersen et al 1985; Treit 1994, 1995). Furthermore, the anxietyreducing actions of systemic benzodiazepines can be blocked by intra-amygdala injection of GABA/benzodiazepine antagonists (Sanders and Shekhar 1995).The amygdala also has high levels of endogenous opioid peptides and opioid receptors (Loughlin et al 1995), and opioid mechanisms have been implicated in many biological functions, including nociception, memory, and fear conditioning (Good and Westbrook 1995;McGaugh et al 1996;Valverde et al 1996). A partial anxiolytic action has been reported following microinjection of morphine into amygdala (File and Rodgers 1979).…”
mentioning
confidence: 99%
“…The amygdala also has high levels of endogenous opioid peptides and opioid receptors (Loughlin et al 1995), and opioid mechanisms have been implicated in many biological functions, including nociception, memory, and fear conditioning (Good and Westbrook 1995;McGaugh et al 1996;Valverde et al 1996). A partial anxiolytic action has been reported following microinjection of morphine into amygdala (File and Rodgers 1979).…”
mentioning
confidence: 99%